Dritter Gentechnologiebericht Analyse einer Hochtechnologie - Berlin-Brandenburgische Akademie der Wissenschaften (Nomos Verlagsgesellschaft mbH & Co. KG, 2015)
"With the Third Gene Technology Report the interdisciplinary research group "Gene Technology Report" of the Berlin-Brandenburg Academy of Sciences and Humanities presents a new edition of comprehensive monitoring on current developments in the field of gene technology in Germany. The book analyzes the state of the latest scientific and technological developments in the field of gene technology using a proven, interdisciplinary approach. The report continues the indicator-based procedure which has been established over the last several years. Six fields of basic research are being discussed: epigenetics in biomedicine, molecular diagnosis in human medicine, research on pluripotent human stem cells, somatic gene therapy, the application of gene technology in plant breeding and agriculture, and the interdisciplinary field of synthetic biology. Core statements and recommendations for action that present the most relevant developments and research trends complete this report. With contributions by: Nediljko Budisa, Julia Diekämper, Silke Domasch, Boris Fehse, Jürgen Hampel, Ferdinand Hucho, Anja Hümpel, Kristian Köchy, Lilian Marx-Stölting, Bernd Müller-Röber, Jens Reich, Hans-Jörg Rheinberger, Hans-Hilger Ropers, Jochen Taupitz, Jörn Walter und Martin Zenke."